Preparation method and application of multi-component copolymerized adhesive with high bonding performance and long-acting mildew resistance
By introducing ferrocene groups and 1,3,4-oxadiazole compounds to construct a chemical crosslinking and mechanical interlocking reinforcement system, the problem of traditional adhesives being prone to mold growth in humid environments is solved, achieving high bonding performance and long-lasting mold resistance, suitable for fields such as engineered wood products and wood-based structures.
Patent Information
- Application Number
- CN202511124122.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-10-31
AI Technical Summary
Traditional adhesives are susceptible to mold in humid environments, leading to performance degradation and the potential release of harmful substances. Furthermore, existing 1,3,4-oxadiazole adhesives are unstable and easily degraded, making it difficult to meet the performance requirements of wood adhesives.
By introducing ferrocene groups and 1,3,4-oxadiazole compounds to synergistically enhance the chemical crosslinking and mechanical interlocking system, a multi-component copolymer adhesive is formed, which improves stability and bonding performance while retaining antifungal and antibacterial properties.
It significantly improves the stability and bonding strength of the adhesive, has long-lasting mildew resistance and excellent water resistance, is suitable for plywood applications in complex environments, and is formaldehyde-free and environmentally friendly.
Smart Images

Figure CN120865820A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of formaldehyde-free adhesives, specifically to a method for preparing and applying a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance. Background Technology
[0002] Traditional adhesives, such as aldehyde-based adhesives, are susceptible to mold growth in humid environments, leading to decreased plywood performance and the release of harmful substances, posing health risks. 1,3,4-Oxadiazole compounds inhibit the synthesis of ergosterol by suppressing fungal cytochrome P-450-dependent enzymes (14α-sterol demethylase, P-450DM). This results in reduced ergosterol content in fungal cell membranes, affecting membrane fluidity and integrity, hindering nutrient transport, and interfering with cell wall synthesis, making fungal cells more vulnerable to external damage. While existing 1,3,4-oxadiazole adhesives possess anti-mold and antibacterial properties, they suffer from poor stability, easy degradation, and uneven mixing. Furthermore, improvements through additives (such as salts or organic compounds) are limited, making it difficult to meet the performance requirements of wood adhesives. This invention significantly improves the stability and bonding performance of adhesives by introducing ferrocene groups and optimizing the molecular structure of 1,3,4-oxadiazole compounds through multi-component copolymerization, while retaining their highly efficient anti-mildew and antibacterial properties, thus solving the defects of traditional adhesives such as easy mold growth and insufficient stability. Summary of the Invention
[0003] This invention overcomes the problem of common trialdehyde adhesives being susceptible to mold in humid environments, aiming to provide a method for preparing and applying a multi-component copolymer adhesive with high bonding performance and long-lasting mold resistance. This invention innovatively provides a method for preparing a 1,3,4-oxadiazole multi-component copolymer adhesive based on ferrocene functional modification by introducing ferrocene groups and synergistic effects with 1,3,4-oxadiazole compounds to construct a chemical crosslinking and mechanical interlocking reinforcement system. This method significantly improves the stability and interfacial adhesion of the adhesive, resulting in an adhesive with high bonding strength, long-lasting mold resistance, and excellent water resistance. Simultaneously, it completely solves the problem of outdoor mold growth in plywood by inhibiting fungal metabolic pathways. Furthermore, the adhesive's thermal stability and compressive strength are significantly improved, and it is formaldehyde-free and environmentally friendly, suitable for fields such as engineered wood products and wood-based structures, with broad industrial application prospects.
[0004] Technical problems to be solved
[0005] Adhesives play a crucial role in numerous fields such as construction, furniture, and packaging. However, traditional adhesives are often susceptible to bacterial and mold growth, leading to a decline in adhesive performance and even affecting the lifespan and safety of the materials they bond. For example, in humid environments, mold easily grows on adhesive surfaces, not only affecting aesthetics but also potentially releasing harmful mycotoxins that threaten human health. Simultaneously, bacterial growth accelerates adhesive aging and decomposition, reducing its bond strength. 1,3,4-Oxadiazole compounds, due to their high anti-mold and antibacterial properties, can solve the problem of mold growth in engineered wood products. Furthermore, they are abundant in variety, raw materials, and catalysts, exhibit good bond strength to various substrates, and their near-zero toxicity makes them suitable for manufacturing wooden furniture, timber-framed buildings, and lightweight panels, contributing to a safer living environment. However, while traditional 1,3,4-oxadiazole organic adhesives have many advantages, they also suffer from poor stability, easy degradation, and uneven mixing with other adhesives. This invention introduces ferrocene groups to synergistically interact with 1,3,4-oxadiazole compounds, constructing a chemical crosslinking and mechanical interlocking reinforcement system through multi-component copolymerization. This results in an adhesive with high bonding strength, long-lasting mildew resistance, and excellent water resistance. At the same time, it completely solves the problem of outdoor mold growth on plywood by inhibiting fungal metabolic pathways.
[0006] Technical solution
[0007] To address the shortcomings of existing technologies, the high-adhesion, long-lasting mildew-resistant multi-component copolymer adhesive of the present invention is made from the following components: ethyl 4-formylbenzoate, 2,4-dinitrophenylhydrazine, ethanol, ferrocene formaldehyde, piperidine, phenolic resin, industrial flour, glacial acetic acid, potassium hydroxide, and water.
[0008] The preparation method described in this invention utilizes the condensation reaction between the amino group in the 1,3,4-oxadiazole ring and the aldehyde group in ferrocene formaldehyde to form an imine intermediate, which is further cyclized to introduce ferrocene groups into the 1,3,4-oxadiazole ring structure. This improves the stability of the organic adhesive. Ferrocene formaldehyde only provides ferrocene groups, without any aldehydes entering the adhesive. The ferrocene-containing 1,3,4-oxadiazole is uniformly added to the phenolic resin, allowing the adhesive to penetrate evenly into the wood, ensuring normal distribution of adhesive components at the bonding interface. High-temperature curing forms a three-dimensional network structure, improving the bonding performance and rheological properties of the system, and contributing to the improvement of the bonding strength and toughness of the phenolic resin adhesive.
[0009] The preparation method of the multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance described in this invention is as follows:
[0010] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compounds: Ethyl 4-formylbenzoate and 2,4-dinitrophenylhydrazine were mixed in ethanol and heated under reflux with glacial acetic acid as a catalyst to obtain an intermediate. The intermediate was then treated with potassium hydroxide solution and recrystallized from an ethanol-water mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring was then mixed with ferrocene formaldehyde in a glacial acetic acid and ethanol mixed solvent with piperidine as a catalyst and heated under reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was then recrystallized from an ethanol-water mixed solvent to generate ferrocene-containing 1,3,4-oxadiazole compounds.
[0011] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, it was first added to water and stirred evenly before ultrasonication to ensure uniform dispersion. The phenolic resin was pretreated with industrial flour to increase its viscosity. Then, the pretreated phenolic resin was added to a reaction vessel and stirred to promote uniform mixing of the adhesive with the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0012] Preferably, in step (1), the mass ratio of ethyl 4-formylbenzoate to 2,4-dinitrophenylhydrazine is 1:(2.8-3.2).
[0013] Preferably, in step (1), the mass ratio of 1,3,4-oxadiazole ring to ferrocene formaldehyde is 1:(6.7-9). Preferably, in step (1), the aldehyde content of ethyl 4-formylbenzoate is not less than 78%, and the activity is 65%.
[0014] Preferably, the ultrasonic-assisted liquid phase stripping time in step (1) is 1-10 hours.
[0015] Preferably, in step (1), the mass ratio of ferrocene-containing 1,3,4-oxadiazole to epoxy resin is 1:(47-62). Preferably, in step (1), the amount of piperidine added is 0.2-0.4% of the mass of ethyl 4-formylbenzoate. Preferably, in step (2), the mass ratio of phenol to formaldehyde in the phenolic resin adhesive is 1:1.94. Preferably, in step (2), the mass ratio of phenol to sodium hydroxide in the phenolic resin adhesive is 1:0.6. Preferably, in step (2), the mass ratio of phenolic resin adhesive to industrial flour is 1:0.45.
[0016] Beneficial technical effects
[0017] Compared with the prior art, the present invention has the following beneficial technical effects:
[0018] 1. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance developed in this invention has excellent bonding strength and high temperature resistance of phenolic resin itself. Combined with the ferrocene group to improve the stability of 1,3,4-oxadiazole ring, the adhesive can significantly enhance weather resistance and long-term bonding performance, and is suitable for plywood applications in complex environments (such as high temperature and high humidity).
[0019] 2. 1,3,4-Oxadiazole compounds inhibit the activity of fungal cytochrome P-450 enzymes, thereby disrupting the integrity of fungal cell membranes. Combined with the inherent low biodegradability and antimicrobial properties of phenolic resins, this further enhances the long-lasting anti-mildew ability of adhesives, especially in humid environments.
[0020] 3. The use of a multi-component copolymer formaldehyde-free modified phenolic resin system avoids the formaldehyde release problem of traditional "three-aldehyde" adhesives (urea-formaldehyde, phenolic, and melamine-formaldehyde). At the same time, the introduction of ferrocene groups does not introduce new aldehyde substances, ensuring the safety of the living environment.
[0021] 4. The adhesive components are normally distributed at the bonding interface, and a three-dimensional network structure is formed after high-temperature curing, which improves the bonding performance and rheological properties of the system, and is beneficial to improving the bonding strength and toughness of phenolic resin adhesives. It significantly improves the compressive strength and mechanical durability of the adhesive, meeting the requirements for high-strength engineered wood products.
[0022] 5. The mature industrial production system of phenolic resin is highly compatible with the preparation process of 1,3,4-oxadiazole compounds, which simplifies the production process. At the same time, the raw materials are readily available (such as ferrocene formaldehyde, piperidine, etc.), which reduces the overall cost and makes it suitable for large-scale promotion. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 This refers to the dry shear strength of the wood-based composite material in this invention. Figure 2 This refers to the wet shear strength of the wood-based composite material in this invention. Figure 3 The antibacterial rate of the wood composite material in this invention. Detailed Implementation
[0024] Unless otherwise specified, the experimental methods used in the following examples are all conventional operating methods.
[0025] Overall plan:
[0026] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance is made from the following components: ethyl 4-formylbenzoate, 2,4-dinitrophenylhydrazine, ethanol, ferrocene formaldehyde, piperidine, phenolic resin, industrial flour, glacial acetic acid, potassium hydroxide, and water.
[0027] Example 1
[0028] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0029] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compound: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 6.3 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a ferrocene-containing 1,3,4-oxadiazole compound.
[0030] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0031] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0032] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0033] Example 2
[0034] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0035] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compounds: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 8.9 g of ferrocene formaldehyde were placed in a mixed solvent of 2.2 g of glacial acetic acid and 24 ml (95%) ethanol. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate ferrocene-containing 1,3,4-oxadiazole compounds.
[0036] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0037] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0038] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0039] Example 3
[0040] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0041] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compound: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml (95%) ethanol, and 2.2 g of glacial acetic acid was added as a catalyst. The mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 16.9 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent, and 2.7 g of piperidine was added as a catalyst. The mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a ferrocene-containing 1,3,4-oxadiazole compound.
[0042] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0043] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0044] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0045] Example 4
[0046] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0047] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compound: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 19.7 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a ferrocene-containing 1,3,4-oxadiazole compound.
[0048] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0049] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0050] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0051] Example 5
[0052] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0053] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compound: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 21.5 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a ferrocene-containing 1,3,4-oxadiazole compound.
[0054] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0055] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0056] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0057] Example 6
[0058] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0059] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compound: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 24.6 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a ferrocene-containing 1,3,4-oxadiazole compound.
[0060] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0061] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0062] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0063] Example 7
[0064] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0065] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compounds: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 29.8 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate ferrocene-containing 1,3,4-oxadiazole compounds.
[0066] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0067] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0068] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0069] Example 8
[0070] A multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, comprising the following steps:
[0071] (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compound: 8.9 g of ethyl 4-formylbenzoate and 15.1 g of 2,4-dinitrophenylhydrazine were thoroughly stirred in 24 ml of 95% ethanol. 2.2 g of glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with 38 ml of (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring and 33.5 g of ferrocene formaldehyde were mixed in an ethanol-water (1:0.45) mixed solvent. 2.7 g of piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a ferrocene-containing 1,3,4-oxadiazole compound.
[0072] (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, firstly, 5.15g of the ferrocene-containing 1,3,4-oxadiazole compound prepared above was added to 50g of water, stirred evenly, and then ultrasonically dispersed. 67.5g of phenolic resin was pretreated with 10.13g of industrial flour to increase viscosity. Then, the pretreated phenolic resin was added to a reaction vessel, and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
[0073] (3) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0074] (4) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0075] Comparative Example 1
[0076] A phenolic resin adhesive, comprising the following steps:
[0077] (1) Preparation of phenolic resin adhesive. Phenol needs to be dissolved by heating beforehand, and 100g of 40% sodium hydroxide is prepared and added slowly using a constant pressure separatory funnel.
[0078] ① Add 100g of phenol, 80g of water and 50g of sodium hydroxide (40% solution) to the reaction flask, and start stirring for 10 minutes.
[0079] ② Add 150g of formaldehyde (37%) slowly over 5-10 minutes, and heat to 80-90℃ for 1 hour;
[0080] ③ Keep warm at 90-95℃ for 50 minutes, then cool down to 70℃ (preheat another water bath to 70℃, first extract the water at 90℃, then add cold water to 75℃, extract the cold water, then pour in the hot water at 70℃, and continue heating the water in the other water bath to 70℃).
[0081] ④ Slowly add 44g of formaldehyde and 10g of sodium hydroxide to the reaction vessel, and raise the temperature to 92±2℃ within 10 minutes;
[0082] ⑤ After reacting for 60 minutes, the viscosity should be the same as that of a Forte 4 cup in 19-21 seconds (or when dropped into water, it should disperse as a thick mist);
[0083] ⑥ Add 40g of urea, stir and cool to 40℃, then discharge.
[0084] (2) Press three-layer poplar plywood and test its performance. The results are listed below. Figure 1 and Figure 2 .
[0085] (3) Its anti-mildew performance was tested, and the results are listed below. Figure 3 .
[0086] The high bonding performance and long-lasting mildew-resistant multi-component copolymer adhesives obtained in Examples 1 to 8, and the adhesive obtained in Comparative Example 1, were used to prepare three-layer plywood with poplar veneer, a moisture content of 5-15%, and dimensions of 30cm*30cm*0.15cm, according to the following process:
[0087] Adhesive application: Apply adhesive to both sides of the core board, with an adhesive application rate of 300-400g / m². 2 ;
[0088] Pressing: Pressure 1MPa, temperature 110-130℃, time 6 minutes.
[0089] The bonding strength of the plywood products produced was tested according to the testing methods in GB / T17657-1999 "Test Methods for Physical and Chemical Properties of Wood-based Panels and Decorative Wood-based Panels". The test results are as follows: Figure 1 and Figure 2 As shown.
[0090] LB solid medium was prepared by dissolving a mixture of yeast powder (0.5 g), tryptophan (1 g), sodium chloride (1 g), and 1.5 g agar powder in 100 g of deionized water, followed by autoclaving. Escherichia coli and Staphylococcus aureus were diluted to 10 CFU / mL with LB liquid medium. 1 mL of bacterial culture was added to each bacterial culture tube, and then to a petri dish containing an equal volume of moistened culture medium from the examples and comparative studies. The mixture was incubated at 37°C for 18 hours, and colony counting was performed. The antibacterial rate (%) was calculated as (experimental group bacterial solution concentration / control group bacterial solution concentration) x 100% to test the produced adhesive products. The test results are shown in Table 1.
[0091] from Figure 1 and Figure 2 As can be seen, the high-adhesion, long-lasting mildew-resistant multi-component copolymer adhesive of this invention is made from the following components: ethyl 4-formylbenzoate, 2,4-dinitrophenylhydrazine, ferrocene formaldehyde, glacial acetic acid, ethanol, piperidine, water, phenolic resin adhesive, and potassium hydroxide. By utilizing a functionally modified ferrocene-containing 1,3,4-oxadiazole compound, it can form a stable mechanical interlocking structure with the phenolic matrix and also undergo covalent / non-covalent interactions with the phenolic resin matrix, thereby forming a strong physical interlocking and multiple chemical cross-linking network structure, which is beneficial to improving the bonding strength and toughness of the phenolic resin adhesive. Experimental results show that the three-layer plywood pressed using the adhesive of this invention has excellent mechanical properties, with a wet shear strength of 1.24-2.12 MPa, which is superior to the comparative example.
[0092] Depend on Figure 1 and Figure 2 It can be seen that, compared with the plywood prepared using the high-adhesion, long-lasting mildew-resistant multi-component copolymer adhesives prepared in Examples 1 to 4, the dry shear strength and wet shear strength gradually increase. It can be observed that with the addition of the functionally modified ferrocene-containing 1,3,4-oxadiazole compound, effective active sites can be generated, forming a strong interfacial interaction between the phenolic resin polymer and the compound, thereby improving the dispersibility of the compound in the adhesive. Utilizing the enhanced interfacial interaction and interfacial adhesion between the compound and plant protein, the plant protein adhesive is synergistically strengthened and toughened, improving the water-resistant bonding performance of the adhesive.
[0093] Compared with Examples 1, 2, and 5, and Examples 6, 7, and 8, the dry shear strength and wet shear strength of the adhesive gradually decreased. This is because the grafting rate of the functionally modified ferrocene-containing 1,3,4-oxadiazole compound gradually remained unchanged, the resulting active sites became saturated, and the excess compound hindered the formation of the modified resin network structure, thus reducing the adhesive's water resistance and bonding performance.
[0094] Compared with Comparative Example 1, the present invention uses a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, prepared by using a functionally modified ferrocene-containing 1,3,4-oxadiazole compound to enhance the water-resistant bonding performance and mildew resistance of the plywood pressed from it. The mildew resistance is significantly better than that of the prior art.
[0095] Therefore, the method for preparing the high-adhesion, long-lasting mildew-resistant multi-component copolymer adhesive of the present invention uses basic raw materials such as ethyl 4-formylbenzoate, 2,4-dinitrophenylhydrazine, ferrocene formaldehyde, glacial acetic acid, ethanol, piperidine, water, phenol, sodium hydroxide, formaldehyde, and potassium hydroxide. By utilizing functionally modified ferrocene-containing 1,3,4-oxadiazole compounds, it can form a stable mechanical interlocking structure with the phenolic matrix and also undergo covalent / non-covalent interactions with the phenolic resin matrix, thereby forming a strong physical interlocking and multiple chemical cross-linking network structure. This yields a high-strength, high-performance, high-adhesion, long-lasting mildew-resistant multi-component copolymer adhesive with good industrial application prospects.
[0096] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance, and its application, characterized in that, It is composed of the following raw materials: ethyl 4-formylbenzoate, 2,4-dinitrophenylhydrazine, ferrocene formaldehyde, glacial acetic acid, ethanol, piperidine, water, phenolic resin adhesive, and potassium hydroxide; wherein the mass ratio of each raw material is 1:(1.1-2.2):(1.2-2.9):(0.2-0.3):(1.3-2.5):(0.2-0.4):appropriate amount:(13.0-22.9):(216.7-285.9):(0.17-0.31).
2. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 1, characterized in that, The mass ratio of the 1,3,4-oxadiazole ring to ferrocene formaldehyde is 1:(6.7-9).
3. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 1, characterized in that, The phenolic resin adhesive has a phenol to formaldehyde mass ratio of 1:1.94 and a phenol to sodium hydroxide mass ratio of 1:0.
6.
4. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 1, characterized in that, The ethyl 4-formylbenzoate has an aldehyde content of not less than 78% and an activity of 65%.
5. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 1, characterized in that, The method for preparing the organic adhesive includes the following steps: (1) Preparation of ferrocene-containing 1,3,4-oxadiazole compounds: Ethyl 4-formylbenzoate and 2,4-dinitrophenylhydrazine were thoroughly stirred in 95% ethanol, glacial acetic acid was added as a catalyst, and the mixture was heated to reflux to obtain an intermediate. The intermediate was treated with (50%) potassium hydroxide solution. The product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate a 1,3,4-oxadiazole ring. The synthesized 1,3,4-oxadiazole ring was reacted with ferrocene formaldehyde in a glacial acetic acid and (95%) ethanol mixed solvent, piperidine was added as a catalyst, and the mixture was heated to reflux. Insoluble impurities were removed by filtration, and the solvent was removed by vacuum distillation to obtain a crude product. The crude product was recrystallized from an ethanol-water (1:0.45) mixed solvent to generate ferrocene-containing 1,3,4-oxadiazole compounds. (2) Preparation of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance: To ensure the dispersibility of the ferrocene-containing 1,3,4-oxadiazole compound in phenolic resin, the ferrocene-containing 1,3,4-oxadiazole compound prepared above was first added to water, stirred evenly, and then ultrasonically dispersed. The phenolic resin was pretreated with industrial flour to increase its viscosity. Then, the pretreated phenolic resin was added to a reaction vessel and stirred to promote uniform mixing of the adhesive and the ferrocene-containing 1,3,4-oxadiazole compound, thus preparing a multi-component copolymer adhesive sample with high bonding performance and long-lasting mildew resistance containing the ferrocene-containing 1,3,4-oxadiazole compound.
6. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 5, characterized in that, The catalyst used in step (3) is piperidine, and the volume ratio of glacial acetic acid to ethanol in the reaction solvent is 1:(10-15).
7. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 1, characterized in that, The adhesive is used for bonding engineered wood panels, wooden furniture, or building materials. It has a dry bonding strength of up to 2.39 MPa, a wet bonding strength of up to 2.12 MPa, an antibacterial rate of ≥90%, and a mildew-proof effect of up to 180 days.
8. The multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance according to claim 1, characterized in that, The concentration of the potassium hydroxide solution is 50%.
9. The application of a multi-component copolymer adhesive with high bonding performance and long-lasting mildew resistance as described in any one of claims 1-8 in the production of high-performance plywood.